Genotypic Correlation between Cases of Clostridium difficile (CDI) with Community-Onset Diagnosis after Recent Hospital Discharge and Their Prior Unit-Based Contacts. (4th October 2017) - Aslam, Anoshé; Brite, Jennifer; McMillen, Tracy; Chow, Hoi Yan; Babady, N Esther; Kamboj, Mini
Abstract: Background: The incubation period of C. difficile infection (CDI) is highly variable. Infections may be diagnosed weeks after initial acquisition of bacterial spores. Such cases of CDI have onset in the community after a recent hospitalization, or upon readmission, and are characterized as community-onset healthcare-facility associated (CO-HCFA) by current surveillance methods. Aim: With the application of multi-locus sequence typing (MLST), our study seeks to characterize genetic concordance between CO-HCFA cases and prior unit-based contacts (donors) sharing the same strain type (ST). Methods: For all laboratory-identified cases of CDI from January 1, 2015, through December 31, 2016, patients with CDI onset within 8 weeks of hospital discharge were included in the study. Infection control database was queried to identify putative donors using the following criteria: previous unit occupants with CDI who had been discharged from the same unit less than 4 weeks, 4–8 weeks, and 8–12 weeks before admission of CO-HCFA cases. Intensity of exposure was further characterized by same room or same unit occupancy. Analysis was restricted to endemic strains at our institution (ST 1, 2, 3, 8, 11 and 42). Results: During the two year period, 1330 cases were diagnosed with a new CDI episode, 425 community-onset (32%), 440 hospital-onset (33%) and 465 CO-HCFA (35%) cases. Among the 314 unique CO-HCFA patients due to endemic strains, there were a total of 92 same unit contacts with a concordant strain type, and 1035 same unit contacts with a discordant strain type. The proportion of concordant same unit occupants did not differ by time between cases ( P = 0.8120). Conclusion: CO-HCFA cases account for a third of all new cases of CDI. Genotypic concordance as potential donors was observed among 8% of all indirect unit based CDI contacts of CO-HCFA cases. This association did not vary significantly as the interval between potential exposure and CDI onset in CO-HCFA cases increased. Disclosures: All authors: No reported disclosures.